(untitled) (Ustozlar uchun, 2026)
This study examines the role and frequency of discourse markers in informal spoken English produced by Uzbek English speakers. The research is based on a corpus of more than 50 YouTube videos, including foreign language learning channels, personal lifestyle vlogs, conversational interviews, and spontaneous speaking content. The total dataset consists of manually transcribed speech, which was carefully analyzed to identify recurring discourse markers and their pragmatic functions. The findings indicate that because, and, like, just, but, and so are the most frequently used discourse markers in informal spoken English. These markers are not only grammatical connectors but also pragmatic tools that regulate discourse flow, manage hesitation, express stance, and enhance conversational naturalness. The study highlights that YouTube-based spoken data provides a rich source for analyzing authentic language use in digital environments.